2021
DOI: 10.52547/jrums.20.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Gratitude and Perceived Social Support and Happiness of Elderly Women in Districts 3, 4, and 5 of Tehran in 2020 during the Epidemic of Covid-19 Disease: A Descriptive Study

Abstract: Background and Objectives:Happiness is a positive psychological variable that can affect the lives of the elderly.Therefore, the present study was conducted to determine the relationship between happiness and social support and appreciation in older women. Materials and Methods:The present study is descriptive. For this study, 384 elderly women in districts 3, 4, and 5 of Tehran in 2020 were selected as the sample by the available sampling method. Gratitude Questionnaire-Six-Item Form, Multidimensional Scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the interviews, they expressed gratitude towards the people around them: their husbands, family, children, friends, neighborhood, communities, members of religious organizations, and their jamaah (congregation). Bayrami et al (2021) found that gratitude and social support are directly related to happiness and can positively predict it, especially in women. Another previous study on gratitude from the gender perspective also led to interesting findings.…”
Section: Discussionmentioning
confidence: 96%
“…In the interviews, they expressed gratitude towards the people around them: their husbands, family, children, friends, neighborhood, communities, members of religious organizations, and their jamaah (congregation). Bayrami et al (2021) found that gratitude and social support are directly related to happiness and can positively predict it, especially in women. Another previous study on gratitude from the gender perspective also led to interesting findings.…”
Section: Discussionmentioning
confidence: 96%
“…Although prolonged human life is considered as one of the major human advances, unfortunately most people who reach old age suffer from several diseases and serious health issues including negative emotions such as depression, anxiety, stress, low self-esteem, low quality of life, and social isolation (3). Physical and psychosocial capabilities mitigate at advanced ages, leading to a decline in happiness in the elderly (5).…”
Section: Introductionmentioning
confidence: 99%